2020
DOI: 10.3390/su12020696
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Concrete as a Sustainable Building Material?

Abstract: The right selection of building materials plays an important role when designing a building to fall within the definition of sustainable development. One of the most commonly used construction materials is concrete. Its production causes a high energy burden on the environment. Concrete is susceptible to external factors. As a result, cracks occur in the material. Achieving its durability along with the assumptions of sustainable construction means there is a need to use an environmentally friendly and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 53 publications
(61 reference statements)
0
34
0
Order By: Relevance
“…Then microorganism will activate the biomineralization process, generating CaCO 3 precipitates which will solidify on the damaged surface, sealing the material. Furthermore, during their activity, the bacteria consume oxygen avoiding corrosion phenomena and increasing the concrete durability [ 29 ]. In terms of mechanical behavior, Thakur et al [ 30 ] revealed an enhanced mechanical strength in bacteria-based concrete than Portland control samples.…”
Section: Co 2 Emission Mitigation Strategies In the Cement Industry: An Overviewmentioning
confidence: 99%
“…Then microorganism will activate the biomineralization process, generating CaCO 3 precipitates which will solidify on the damaged surface, sealing the material. Furthermore, during their activity, the bacteria consume oxygen avoiding corrosion phenomena and increasing the concrete durability [ 29 ]. In terms of mechanical behavior, Thakur et al [ 30 ] revealed an enhanced mechanical strength in bacteria-based concrete than Portland control samples.…”
Section: Co 2 Emission Mitigation Strategies In the Cement Industry: An Overviewmentioning
confidence: 99%
“…These are not only short-lived, but they also have an anisotropy coefficient of 7-9 or more, unlike prototypes with an anisotropy coefficient of 2-3 [49]. An increase in the tensile strength of the masonry with the proposed compositions by 3-5 times is elucidated by the microstructure of the region of contact, for instance, ceramic bricks and mortar [50] (Figure 4). The developed masonry mortar and the wall material are practically a single monolith; in the design of a traditional binder, the interfacial transition (contact) zone is clearly visible, which is the weakest point of the samples [51,52].…”
Section: The Affinity Microstructuresmentioning
confidence: 99%
“…A novel class of material that is gaining popularity among researchers in the field of repair and self-healing of concrete and cementitious materials is bacteria-based repair agents, which, according to some authors, represent the frontier in the field of material science [2]. Bacterial concrete has also shown the potential to become an effective response to growing sustainability requests [22]. The basic principle of these repair techniques (Figure 3) is to utilise the ability of some bacterial species to induce precipitation of calciumcarbonate inside the cementitious matrix.…”
Section: Different Approaches To (Self-)healing and Repair With Focus On Bacteria-based Solutionsmentioning
confidence: 99%